Insights into acetate-mediated copper homeostasis and antioxidant defense in lentil under excessive copper stress. (March 2020) - Hossain, Md. Shahadat; Abdelrahman, Mostafa; Tran, Cuong Duy; Nguyen, Kien Huu; Chu, Ha Duc; Watanabe, Yasuko; Hasanuzzaman, Mirza; Mohsin, Sayed Mohammad; Fujita, Masayuki; Tran, Lam-Son Phan
Abstract: Gradual contamination of agricultural land with copper (Cu), due to the indiscriminate uses of fungicides and pesticides, and the discharge of industrial waste to the environment, poses a high threat for soil degradation and consequently food crop production. In this study, we combined morphological, physiological and biochemical assays to investigate the mechanisms underlying acetate-mediated Cu toxicity tolerance in lentil. Results demonstrated that high dose of Cu (3.0 mM CuSO4 . 5H2 O) reduced seedling growth and chlorophyll content, while augmenting Cu contents in both roots and shoots, and increasing oxidative damage in lentil plants through disruption of the antioxidant defense. Principle component analysis clearly indicated that Cu accumulation and increased oxidative damage were the key factors for Cu toxicity in lentil seedlings. However, acetate pretreatment reduced Cu accumulation in roots and shoots, increased proline content and improved the responses of antioxidant defense (e.g. increased catalase and glutathione- S- transferase activities, and improved action of glutathione-ascorbate metabolic pathway). As a result, excess Cu-induced oxidative damage was reduced, and seedling growth was improved under Cu stress conditions, indicating the role of acetate in alleviating Cu toxicity in lentil seedlings. Taken together, exogenous acetate application reduced Cu accumulation in lentil roots and shoots and mitigated oxidative damage by activating the antioxidant defense, which were the major determinants for alleviating Cu toxicity in lentil seedlings. Our findings provide mechanistic insights into the protective roles of acetate in mitigating Cu toxicity in lentil, and suggest that application of acetate could be a novel and economical strategy for the management of heavy metal toxicity and accumulation in crops. Graphical abstract: Image 1 Highlights: Effects of acetate on improvement of lentil performance under Cu stress were studied. Exogenous acetate improved photosynthetic pigments and osmoprotection in Cu-stressed plants. Acetate alleviated Cu-induced oxidative damage by modulating antioxidant system of lentil. Cu accumulations in both roots and shoots of lentil were decreased by acetate treatment. Acetate application could be a low cost solution for farmers to manage Cu toxicity in plants. Abstract : This study showed that acetate application can protect lentil plants from the toxicity of excess Cu by enhancing photosynthetic capacity, activating antioxidant defense, maintaining osmotic adjustment and reducing Cu accumulation in both shoots and roots. The acetate treatment could be recommended to the farmer as low-cost and effective method for the management of heavy metal toxicity in lentils and other crop plants.